2014
DOI: 10.1002/2013ja019537
|View full text |Cite
|
Sign up to set email alerts
|

Deflected propagation of a coronal mass ejection from the corona to interplanetary space

Abstract: Among various factors affecting the space weather effects of a coronal mass ejection (CME), its propagation trajectory in the interplanetary space is an important one determining whether and when the CME will hit the Earth. Many direct observations have revealed that a CME may not propagate along a straight trajectory in the corona, but whether or not a CME also experiences a deflected propagation in the interplanetary space is a question, which has never been fully answered. Here by investigating the propagat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 78 publications
5
70
0
Order By: Relevance
“…The speed, density, pressure, magnetic field, and shock structure can all change as the ICME expands and interacts both with the ambient solar wind as well as with various disturbances within it. In particular, through observational and modeling work, studies have shown that during propagation the flux rope may kink and deform [ Manchester et al , ], reconnection/erosion of internal ICME magnetic flux may occur [ Lavraud et al , ; Ruffenach et al , ], and the ICME may also get deflected [ Manchester et al , ; Kay et al , , ; Wang et al , ] and rotated [ Kliem et al , ; Lynch et al , ]. A recent CME event study by Nieves‐Chinchilla et al [] using both in situ and remote sensing observations from STEREO, SOHO, MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER), and Wind showed evidence for significant reorientation of the flux rope axis.…”
Section: Introductionmentioning
confidence: 99%
“…The speed, density, pressure, magnetic field, and shock structure can all change as the ICME expands and interacts both with the ambient solar wind as well as with various disturbances within it. In particular, through observational and modeling work, studies have shown that during propagation the flux rope may kink and deform [ Manchester et al , ], reconnection/erosion of internal ICME magnetic flux may occur [ Lavraud et al , ; Ruffenach et al , ], and the ICME may also get deflected [ Manchester et al , ; Kay et al , , ; Wang et al , ] and rotated [ Kliem et al , ; Lynch et al , ]. A recent CME event study by Nieves‐Chinchilla et al [] using both in situ and remote sensing observations from STEREO, SOHO, MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER), and Wind showed evidence for significant reorientation of the flux rope axis.…”
Section: Introductionmentioning
confidence: 99%
“…Observations and simulations show that the largest CME deflections and rotations occur in the corona (Byrne et al, ; Isavnin et al, ; Kay, Gopalswamy, Xie, et al, ; Kay, Opher, et al, ), but observations suggest that interplanetary deflections may also occur (e.g., Liu et al, ; Lugaz et al, ; Wang et al, , ). Multiple interplanetary coronal mass ejections (ICMEs) interacting can lead to deflections (e.g., Lugaz et al, , ; Xiong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of previous studies of fitting locally observed MCs simply assumed that MCs propagate radially from the Sun, which means that boldvcvXtrueboldX̂. However, statistical and case studies of the propagation and geoeffectiveness of CMEs suggested that CME may experience a deflected propagation in interplanetary space [ Wang et al , ; Kilpua et al , ; Rodriguez et al , ; Lugaz , ; Isavnin et al , , ]. It will obviously provide a nonradial component of the linear propagation motion.…”
Section: Introductionmentioning
confidence: 99%